Dating and interpreting the past in the Western Roman Empire (Oxbow Books, 2012)
This volume presents a collection of more than 30 papers in honour of one of Europe's leading scholars on Roman pottery, Brenda Dickinson. Divided into thematic sections, papers are mostly concerned with her principal area of study, samian, but also touch on Brenda's other interests